The Effect Of Financial Literatur On Financial Welfare with Financial Management Behavior as a Mediation in The Papua Mama Market - Abdul Rashid; Zakaria Zakaria; Saling S; Fachruddin Pasalo; Jolius Saroge (Trunojoyo University of Madura, 2022)
This study aims to determine the effect of financial literacy on financial welfare with financial management behavior as a mediating variable in the Papuan Mama-mama Market. The population in this study are individual traders at the Mama-Mama Papua market which are currently registered and verified as many as 140 traders. Based on the Slovin formula, the number of samples taken was 105 people using the purposive sampling technique. In this study, the data analysis method used was structural equation modeling-partial least squares (SEM-PLS) using SmartPLS software.The results show that Financial Literacy has a positive and significant effect on Financial Welfare, Financial Literacy has a positive and significant effect on Financial Behavior, Financial Behavior has a positive and significant impact on Financial Welfare and Financial Behavior can mediate between financial literacy and financial well-being in the Papuan mama-mama market.